2016
DOI: 10.1083/jcb.201507099
|View full text |Cite
|
Sign up to set email alerts
|

RECQ5 helicase promotes resolution of conflicts between replication and transcription in human cells

Abstract: Urban et al. show that RECQ5 DNA helicase promotes RAD18-dependent PCNA ubiquitination and the processing of replication intermediates upon collisions between replication and transcription complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 37 publications
5
69
0
Order By: Relevance
“…Furthermore, MRN loss reduces PCNA ubiquitination and is epistatic with knockdown of RAD18, an E3 ubiquitin ligase for PCNA and known activator of the FA pathway 43 . These observations are consistent with the literature in the context of DNA damage repair, where RAD18 requires RECQL5 binding to stimulate PCNAubiquitination 47 , and where RECQL5 recruitment to damage sites is dependent on the MRN complex 48 . Our data coalesces with the literature in a model where MRN is an early actor at R-loop stalled forks, and coordinates the recruitment of FA pathway components through a cascade of events ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, MRN loss reduces PCNA ubiquitination and is epistatic with knockdown of RAD18, an E3 ubiquitin ligase for PCNA and known activator of the FA pathway 43 . These observations are consistent with the literature in the context of DNA damage repair, where RAD18 requires RECQL5 binding to stimulate PCNAubiquitination 47 , and where RECQL5 recruitment to damage sites is dependent on the MRN complex 48 . Our data coalesces with the literature in a model where MRN is an early actor at R-loop stalled forks, and coordinates the recruitment of FA pathway components through a cascade of events ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Two of them, c.233C>T, p.Pro78Leu and c.539G>A, p.Arg180His were located in the helicase domain of RECQL5 and we demonstrated that they affected its activity by using a functional assay previously described (Figure ; Newman et al, ). It has been reported that the helicase activity of RECQL5 is necessary to exert its function in the resolution of replication‐transcription conflicts and the prevention of spurious HR (Urban et al, ). Taking into account that most BC susceptibility genes described so far are directly or indirectly involved in HR, we propose that variants in RECQL5 affecting HR regulation could be associated with BC risk, although further functional assays testing the actual effect on altering the DNA would be necessary to draw more definite conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this coordination is actively enforced by trans-acting factors, especially within CFSs that are prone to transcription stress, remains an important question. One known factor acting on the conflict resolution is RECQL5, a DNA helicase that associates with both RNAPII and PCNA (4345); of note, RECQL5 depletion leads to uncontrolled elongation of RNAPII, with higher levels of RNAPII pausing and arrest globally at the transcription regions (45). We postulate that BMI1 and RNF2 may impose similar control over RNAPII elongation at CFSs.…”
Section: Discussionmentioning
confidence: 99%